Penerapan Prinsip Keterbukaan dan Akuntabilitas dalam Mewujudkan Good Governance dalam Pengelolaan Dana BOS di SDN 021 Kota Bandung. - Mardiansyah, Muhammad Abdillah Faqih; Rosmiati, Mia (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2024)
This research study explores the implementation of the principles of transparency and accountability in the administration of BOS funds at SDN 021 Bandung City.  The research was conducted using a descriptive qualitative method, with the primary data collection process taking place in 2023. The findings of this study indicate that the implementation of accountability in the management of BOS funds is proceeding satisfactorily, with evidence of community involvement. However, the absence of consistent regulatory frameworks resulted in the emergence of several challenges in the management of BOS funds.